Student alienation and perceived organizational culture: A correlational study - Rajvi Trivedi; G. S. Prakasha (International Journal of Evaluation and Research in Education (IJERE), 2021)
It is generally expected that the students are supposed to gain an engaging and enriching experience throughout their journey of higher education. The educational institutions have to take up the responsibility to ensure that students are engaged meaningfully and are in a state of well-being. However, in the present scenario, students at colleges and universities have started to feel alienated from the campus life. Research shows that alienation levels are rising among the youth. Factors like stress, coping mechanism, restrictive parental behavior, peer pressure, academic performance, and organizational culture have an impact on alienation among the students. This study attempts to understand the relationship between student alienation and organizational culture in an educational institution. The study employed a descriptive correlational design and collected data from 600 under graduate students studying in a university. The study used student alienation scale and organizational culture assessment instrument to collect the survey data. Study revealed that there is a negative correlation between student alienation and organizational culture. There were 30% variation in student alienation is explained by different types of organizational culture. Clan culture reduces student alienation compared to hierarchy culture. The researchers urge for further research to identify ideal organizational cultures that can promote student engagement and student well-being.